Quantum Field Theory Free of Divergences (Global Journal of Science Frontier Research, 2020)
The paper proposes the option of combining gravity and quantum field theory, which avoids the divergences in the latter. The consideration is carried out on the example of calculating the Casimir force between two endless parallel plates for a scalar massive field. The results of traditional solutions containing the divergences of the energy of quantum fluctuations of a vacuum and methods of eliminating them by known ways are presented. It is shown that taking into account the mass of plates, which leads to a curvature of space-time, allows us to obtain the same result without divergence by calculating the Riemann zeta function in the curved metric.
Keywords: quantum field theory; divergences; renormalization; casimir force; metric; riemann zeta function; einstein equations